Talent Attraction Amid Digital Competition and Engagement Challenges: A Literature Review Study - Teguh Aribowo; Muhammad Sukri Husnanto; I Made Sukresna (Arthatama: Journal of Business Management and Accounting, 2025)
The rise of digital competition has intensified the demand for high-quality IT talent, presenting challenges in attracting and engaging young professionals. In Indonesia, state-owned enterprises like Bank Rakyat Indonesia (BRI) must compete with tech companies and startups for digital talent. This literature review examines the Brilian Future Leader Program (BFLP) IT Specialist Track as a strategic response to the talent war and engagement issues. Using frameworks such as employer branding, person-organization fit, and strategic talent development, the review explores internal and external factors shaping IT talent’s perceptions of BRI as an employer. Benchmarking is conducted against digital talent programs at Gojek, Tokopedia (GOTO Group), and Telkom Indonesia, focusing on key features such as fast-track leadership, agile work environments, and project-based learning. These insights offer practical recommendations for enhancing BFLP’s attractiveness and engagement, especially among Gen Z and millennials. A conceptual model is proposed, integrating organizational values, leadership opportunities, and employer reputation to explain how talent attraction and engagement are interconnected. This foundation supports future qualitative research and guides improvements in program design, employer communication, and talent positioning in Indonesia’s competitive digital labour market.